Energy supply shocks' nonlinearities on output and prices - Roberto A. De Santis; Tommaso Tornese (European Central Bank (ECB), 2023)
We use a Bayesian Threshold Vector Autoregression model identified through sign and narrative restrictions to uncover non-linearities in the propagation of energy supply shocks. We find that the transmission of energy supply shocks on consumer prices is stronger in high-inflation regimes, supporting nonlinear models. The faster pass-thorough of energy supply shocks to consumer prices (excl. energy) cushions the drop in output in the short term. Energy supply shocks have a stronger impact on output in the medium-term with manufacturing being more adversely affected than GDP. Large energy supply shocks shift the economy to another state but after two and half years the mean-reversion to lower inflation implies a more moderate transmission mechanism, highlighting the importance of state-dependent impulse responses. The energy supply shocks between July 2021 and June 2022 are massive amounting to 3.9 standard deviations on average each month.
Keywords: C32; E32; 330; Business cycles; energy shocks; non-linearities; TVAR; narrative identification